Visual Discrepancy Adaptation Process for Reaching Movement in Children with Learning Disabilities - TAKAHASH, Makoto; GOTO, Kohtaro; MAEDA, Katsutoshi; MUROHASHI, Harumitsu (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
In this study, we measured the ability of children with learning disabilities (LD) to adapt to changes when reaching for visual targets. The rotation and reverse motions of the cursor, representing the subject's hand position, resulted in a change in visual feedback. In the experiment, we measured the changes in adaptation ability for two groups of children, children with LD and normal children, when rotation and reverse motions were varied and the distance from the body to starting point was varied. The results showed the adaptability of children with LD differs with that of normal children in right and left reversed tasks. The motor ability of children with LD was significantly lower even when identical rotation and reverse motions were used for the two groups of children in an exocentric task. The results suggest the probability of a reduced ability or functional impairment in the brain function of children with LD when perceiving depth.